A STATIC CALIBRATION OF MEMS 3-AXIS ACCELEROMETER USING A GENETIC ALGORITHM - Marin MARINOV; Zhivo PETROV (Scientific Journal of Silesian University of Technology. Series Transport)
In this paper, a procedure for MEMS accelerometer static calibration using a genetic algorithm, considering non-orthogonality was presented. The results of simulations and real accelerometer calibration are obtained showing high accuracy of parameters estimation.